A novel predictive strategy for the incidence of postoperative neurocognitive dysfunction in elderly patients with mild cognitive impairment - Liang, Yueying; Xin, Xi; Wang, Hongyan; Hua, Wei; Wu, Yi; Wang, Xinyi; Li, Ping; Zhou, Tong; Wang, Haiyun (Frontiers in Aging Neuroscience, 2022)
Objective: Preoperative levels of cognition-related biomarkers and intraoperative cerebral ischemia and hypoxia might cause postoperative neurocognitive dysfunction (PND). The aim of this study was to evaluate the predictive ability of preoperative plasma biomarkers along with cerebral oxygen saturation (SctO2) for the incidence of PND in elderly patients with mild cognitive impairment (MCI). Methods: 210 patients aged 65–80 years undergoing spinal surgery were randomly assigned to three groups (n=70 each): propofol, sevoflurane, and propofol/sevoflurane as anesthesia maintenance protocols. Propofol was administrated target-controlled infusion of 4 μg/mL (group P), the minimum alveolar concentration (MAC) of inhalation anesthetic sevoflurane was 1.3 (group S), and propofol was injected with a target-controlled plasma concentration of 1.2 μg/mL, accompanied by sevoflurane inhalation 0.7 MAC (group PS). Cognitive function was evaluated one day preoperatively and on the seventh day postoperatively. Preoperative levels of amyloid β-40 (Aβ-40), Aβ-42, total tau protein (T-tau), phosphorylated tau protein (P-tau), and triggering receptors on myeloid cells-2 (TREM2) were investigated. SctO2 was monitored intraoperatively. Results: Aβ-42 had the strongest significant correlation with preoperative MoCA score. The value of Aβ-42 associated with a high risk of PND was 28.34 pg/mL, and the area under the curve (AUC) was predicted to be 0.711. When the preoperative level of Aβ-42 was 28.34 pg/mL, SctO2max% was 9.92%. The AUC was predicted to be 0.872, and the sensitivity and specificity were 0.833 and 0.841, respectively. Conclusion: Under the conditions of preoperative Aβ-42 less than 28.34 pg/mL, the intraoperative fluctuation range of cerebral oxygen saturation should be maintained within 9.92% to reduce the occurrence of PND in geriatric patients with MCI.